Decolonising the Study Tour: An Ethnography of a Student Internship with a New Delhi NGO. (3rd September 2021) - Gilbertson, Amanda; Parris-Piper, Naomi; Robertson, Nicole
ABSTRACT: Although intended to improve students' intercultural competence and global-mindedness, study tours can reinforce assumptions and accentuate social and political hierarchies. Study tours involving students from the Global North interning with development organisations in the Global South are at risk of embodying the pitfalls of volunteer tourism – producing simplistic understandings of the Global South as a place of need, and of development as something that comes from outside the Global South. This paper presents the results of an ethnography of a study tour that involved Australian undergraduates interning with an NGO in New Delhi, India. Evidence from this study tour suggests that making the potential neo-colonial or 'White Saviour' dynamics of the tour an explicit focus of assessment is an effective strategy for ensuring students engage with the social, economic and political positioning of the tour. Further, local host organisations can act strategically to maximise the value of volunteer interns when the program is structured according to the principles of participatory development.